Predominance of heavily calcified coccolithophores at low CaCO3 saturation during winter in the Bay of Biscay - Helen Elizabeth Katie Smith; Toby Tyrrell; Anastasia Charalampopoulou; Cynthia Dumousseaud; Oliver J Legge; Sarah Birchenough; Laura Rachel Pettit; Rebecca Garley; Sue E Hartman; Mark C Hartman; Navjit Sagoo; Chris J Daniels; et al. (PANGAEA, 2012)
Coccolithophores are an important component of the Earth system, and, as calcifiers, their possible susceptibility to ocean acidification is of major concern. Laboratory studies at enhanced pCO2 levels have produced divergent results without overall consensus. However, it has been predicted from these studies that, although calcification may not be depressed in all species, acidification will produce "a transition in dominance from more to less heavily calcified coccolithophores" [Ridgwell A, et al., (2009) Biogeosciences 6:2611-2623]. A recent observational study [Beaufort L, et al., (2011) Nature 476:80-83] also suggested that coccolithophores are less calcified in more acidic conditions. We present the results of a large observational study of coccolithophore morphology in the Bay of Biscay. Samples were collected once a month for over a year, along a 1,000-km-long transect. Our data clearly show that there is a pronounced seasonality in the morphotypes of Emiliania huxleyi, the most abundant coccolithophore species. Whereas pH and CaCO3 saturation are lowest in winter, the E. huxleyi population shifts from <10% (summer) to >90% (winter) of the heavily calcified form. However, it is unlikely that the shifts in carbonate chemistry alone caused the morphotype shift. Our finding that the most heavily calcified morphotype dominates when conditions are most acidic is contrary to the earlier predictions and raises further questions about the fate of coccolithophores in a high-CO2 world.
Supplement to: Smith, HEK et al. (2012): Predominance of heavily calcified coccolithophores at low CaCO3 saturation during winter in the Bay of Biscay. Proceedings of the National Academy of Sciences, 109(23), 8845-8849, https://doi.org/10.1073/pnas.1117508109